OPTIMALISASI FUNGSI PENGANGGARAN DPRD DALAM PRESPEKTIF GOOD GOVERNANCE PADA DEWAN PERWAKILAN RAKYAT DAERAH KOTA BATU - Dwi Sofian, Octa; Rulliansyah, Iqbal; Dewantara, Cicilia Evie; Zulkarnaen, M. Ivan (STIA MALANG, 2025)
This study aims to determine the optimization of the DPRD budgeting function in the perspective of good governance in the Batu City DDPRD. The problem is focused on optimizing budgeting which includes: community participation, accountability, transparency and value of money. As well as inhibiting factors that refer to the government's internal control system (SPIP). This study refers to the concept and elements of good governance as an analysis of the discussion of the problem. The research method used is descriptive qualitative by analyzing budgeting optimization using elements of good governance. Data were collected through interviews with Batu City DPRD Members, Mrs. Susanti Leverika, who serves as a member of Commission C. This study concludes that in optimizing budgeting, the Batu City DPRD has implemented the principles of good governance and there needs to be budget integration in evaluation.